Effect of hand grip exercise on finger dexterity in geriatric population using nine-hole peg board test: A pilot study - PUSHPA R. DHOTE,; MANEESHA S. DESHPANDE,; KIRAN A. MENDHE, (International Journal of Pharma and Bio Sciences, 2017)
Hands are used to grasp, move and exert force to perform various functions. Human manual function is largely reflected by skillful use of the fingers in grasping, lifting, and manipulating objects between the pulps of thumb and one of the four fingers. Its dysfunction exerts a direct impact on functional independence. Elderly individuals have great difficulties in their daily life due to age related loss of manual dexterity. A pilot study was conducted to observe the effect of hand grip exercises on finger dexterity in 20 geriatric individual aged 65 to 75 years with right handed dominance. These individuals were assessed for finger dexterity pre and post exercise intervention for a week. Outcome measures used were Finger dexterity score in seconds with nine-hole pegboard test and grip strength in kilograms with hand dynamometer. Statistical significant improvement in dexterity scores and grip strength were observed in all the participants. Post exercise intervention utilized in this scenario has effectively improved the finger dexterity in elderly which can be helpful to improve their quality of life and confidence.